The evolution of religion and morality: a synthesis of ethnographic and experimental evidence from eight societies - Purzycki, Benjamin Grant (Religion, brain & behavior, 2018)
Understanding the expansion of human sociality and cooperation beyond kith and kin remains an important evolutionary puzzle. There is likely a complex web of processes including institutions, norms, and practices that contributes to this phenomenon. Considerable evidence suggests that one such process involves certain components of religious systems that may have fostered the expansion of human cooperation in a variety of ways, including both certain forms of rituals and commitment to particular types of gods. Using an experimental economic game, our team specifically tested whether or not individually held mental models of moralistic, punishing, and knowledgeable gods curb biases in favor of the self and the local community, and increase impartiality toward geographically distant anonymous co-religionists. Our sample includes 591 participants from eight diverse societies - iTaukei (indigenous) Fijians who practice both Christianity and ancestor worship, the animist Hadza of Tanzania, Hindu Indo-Fijians, Hindu Mauritians, shamanist-Buddhist Tyvans of southern Siberia, traditional Inland and Christian Coastal Vanuatuans from Tanna, and Christian Brazilians from Pesqueiro. In this article, we present cross-cultural evidence that addresses this question and discuss the implications and limitations of our project. This volume also offers detailed, site-specific reports to provide further contextualization at the local level.